Insula volumes in patients with schizoaffective disorder - Atmaca, Murad; Bakis, Dilek; Korkmaz, Sevda; Yildirim, Hanefi (Juan Jose Lopez-Ibor Foundation, 2022)
We aimed to investigate insula volumes in patients with schizoaffective disorder with the motivation that schizoaffective disorder has strong resemblance of clinical presentaion with schizophrenia and bipolar disorder and that there have been studies on insula volumes in patients with schizophrenia and bipolar disorder but not in patients with schizoaffective disorder. We hypothesized that patients with schizoaffective disorder would have similar alterations in regard to insula volumes. Eighteen patients with schizoaffective disorder and nineteen healthy controls were included into the study. Insula volumes were measured by using the MRI. the mean volumes of the insula region for both sides were statistically significant smaller in patients with schizoaffective disorder compared to those of healthy ones (P<0.001). In conclusion, our findings suggest that patients with schizoaffective disorder had reduced volumes of the insula region. Beacuse of some limitations, it is required to replicate our present results in this patient group.
Keywords: Schizoaffective disorder; MRI; volumes; insula